2019
DOI: 10.1016/j.jenvman.2019.109493
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment valorisation by simultaneously removing and recovering phosphate and ammonia from municipal effluents using a mechano-thermo activated magnesite technology

Abstract: Phosphate and nitrate enrichment largely impair aquatic ecosystem functions and services, thus comprising an emerging problem of environmental concern. The problem pertains to developing countries where phosphate and nitrate discharge to surface water is on the rise due to a rapid growth in population. Herein, these pollutants (phosphate and ammonia) were removed from real municipal wastewater using a simple, fast, and cost-effective process. Raw cryptocrystalline magnesite, a mineral abundant in South Africa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Specifically, it has been reported that the growth of Mg 3 (PO 4 ) 2 was observed when pH level was higher than 9.5 based on the results of XRD (Hu et al, 2019; Yan & Shih, 2016). Moreover, the increase in pH level would result in the precipitation of Mg(OH) 2 according to XRD spectra (Mavhungu et al, 2019). Therefore, the optimal pH level for phosphorus removal from struvite precipitation is 9.5 in the current study, which were in agreement with the results of previous studies (Li et al, 2019; Shalaby & El‐Rafie, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it has been reported that the growth of Mg 3 (PO 4 ) 2 was observed when pH level was higher than 9.5 based on the results of XRD (Hu et al, 2019; Yan & Shih, 2016). Moreover, the increase in pH level would result in the precipitation of Mg(OH) 2 according to XRD spectra (Mavhungu et al, 2019). Therefore, the optimal pH level for phosphorus removal from struvite precipitation is 9.5 in the current study, which were in agreement with the results of previous studies (Li et al, 2019; Shalaby & El‐Rafie, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The first stage of the treatment process is the synthesis of struvite by means of thermally activated cryptocrystalline magnesite (calcined magnesite thereafter). The raw cryptocrystalline magnesite activation process, along with the main characteristics of the activated cryptocrystalline magnesite can be found in [1]. The conditions that optimize struvite synthesis, both in terms of pollutants removal and environmental sustainability, were adopted using the results of previous works of our group [1,20].…”
Section: Synthesis Of Struvitementioning
confidence: 99%
“…The raw cryptocrystalline magnesite activation process, along with the main characteristics of the activated cryptocrystalline magnesite can be found in [1]. The conditions that optimize struvite synthesis, both in terms of pollutants removal and environmental sustainability, were adopted using the results of previous works of our group [1,20]. Specifically, struvite was synthesized at 30 minutes of equilibration time, using a 0.5 g calcined magnesite to 500 mL wastewater ratio (i.e.…”
Section: Synthesis Of Struvitementioning
confidence: 99%
See 2 more Smart Citations